ON THE CONVERGENCE THEOREMS OF THE McSHANE INTEGRAL FOR RIESZ-SPACES-VALUED FUNCTIONS DEFINED ON REAL LINE - Ansori, Muslim; Sumanto, Yosephus D.; Dewi, Novi Rustiana (Department of Mathematics Education, Faculty of Mathematics and Natural Sciences, UNY, 2007)
This paper is a partial result of our researchs in the main topic